Rusty's Train Ride - Heather Amery (London Usborne Publishing, 2004)
Dolly the cart horse saves the day in this fourth title in the Farmyard Tales stories. Featuring two levels of texts, these stories are perfect for reading aloud to children aged 2+ and are suitable as easy, self-readers for those aged four and over.'
Keywords: EY - RM -- EY - RM